GASP – XX. From the loose spatially resolved to the tight global SFR–mass relation in local spiral galaxies. Issue 2 (4th July 2019) - Vulcani, Benedetta; Poggianti, Bianca M; Moretti, Alessia; Franchetto, Andrea; Gullieuszik, Marco; Fritz, Jacopo; Bettoni, Daniela; Tonnesen, Stephanie; Radovich, Mario; Jaffé, Yara L; McGee, Sean; Bellhouse, Callum; et al.
ABSTRACT: Exploiting the sample of 30 local star-forming, undisturbed late-type galaxies in different environments drawn from the GAs Stripping Phenomena in galaxies with MUSE (GASP), we investigate the spatially resolved star formation rate–mass (Σ _SFR –Σ _* ) relation. Our analysis includes also the galaxy outskirts (up to >4 effective radii, r e ), a regime poorly explored by other Integral Field Spectrograph surveys. Our observational strategy allows us to detect H α out to more than 2.7 r e for 75 per cent of the sample. Considering all galaxies together, the correlation between the Σ _SFR and Σ _* is quite broad, with a scatter of 0.3 dex. It gets steeper and shifts to higher Σ _* values when external spaxels are excluded and moving from less to more massive galaxies. The broadness of the overall relation suggests galaxy-by-galaxy variations. Indeed, each object is characterized by a distinct Σ _SFR –Σ _* relation and in some cases the correlation is very loose. The scatter of the relation mainly arises from the existence of bright off-centre star-forming knots whose Σ _SFR –Σ _* relation is systematically broader than that of the diffuse component. The Σ _SFR –Σ _tot gas (total gas surface density) relation is as broad as the Σ _SFR –Σ _* relation, indicating that the surface gas density is not a primary driver of the relation. Even though a large galaxy-by-galaxy variation exists, mean Σ _SFR and Σ _* values vary of at most 0.7 dex across galaxies. We investigate the relationship between the local and global SFR– M * relation, finding that the latter is driven by the existence of the size–mass relation.